2017
DOI: 10.1021/acs.organomet.7b00704
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum-Catalyzed Enantioselective Synthesis of Planar-Chiral (η5-Phosphacyclopentadienyl)manganese(I) Complexes and Application in Asymmetric Catalysis

Abstract: Enantioselective desymmetrization of C s -symmetric (η 5 -2,5-dialkenylphospholyl)(allyldiphenylphosphine)manganese(I) dicarbonyl complexes 1 was realized by molybdenum-catalyzed asymmetric ringclosing metathesis (ARCM), and the corresponding bridged planar-chiral phosphacymantrene derivatives 2 were obtained in good yields with excellent enantioselectivity. The enantioselectivity of the ARCM reaction was strongly influenced by the structures of the phospholyl-bound alkenyl groups, and the highest enantioselec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Leaving compound 6a in a standard NMR tube for several days exposed to natural light led to a good but not full conversion to the [2+2] head-to-head dimer 7a as shown by 31 P NMR. It has previously been shown that the coupling constant 1 J Se-P can provide information on the -donor ability of phospholes [4][5][6][7][29][30][31][32]. According to Table 5, phosphole 1b having the trimethylsilyl groups in positions 2 and 4 is the strongest -donor as 6b has the smallest coupling constant with 716 Hz, close to the value for 1phenyl-3,4-dimethylphosphole (713 Hz).…”
Section: Thiooxophospholesmentioning
confidence: 78%
See 3 more Smart Citations
“…Leaving compound 6a in a standard NMR tube for several days exposed to natural light led to a good but not full conversion to the [2+2] head-to-head dimer 7a as shown by 31 P NMR. It has previously been shown that the coupling constant 1 J Se-P can provide information on the -donor ability of phospholes [4][5][6][7][29][30][31][32]. According to Table 5, phosphole 1b having the trimethylsilyl groups in positions 2 and 4 is the strongest -donor as 6b has the smallest coupling constant with 716 Hz, close to the value for 1phenyl-3,4-dimethylphosphole (713 Hz).…”
Section: Thiooxophospholesmentioning
confidence: 78%
“…According to Table 5, phosphole 1b having the trimethylsilyl groups in positions 2 and 4 is the strongest -donor as 6b has the smallest coupling constant with 716 Hz, close to the value for 1phenyl-3,4-dimethylphosphole (713 Hz). The value for compound 6a is smaller compared to the corresponding 1,2,5triphenylselenooxophosphole (742 Hz) [4][5][6][7], indicating a certain influence of the position of the ring substituents on the -donor ability. Interestingly, the dimer 7a has a considerably higher coupling constant with 759 Hz.…”
Section: Thiooxophospholesmentioning
confidence: 99%
See 2 more Smart Citations
“…The enantioselective desymmetrization of C s ‐symmetric (η 5 ‐2,5‐dialkenylphospholyl)(allyldiphenylphosphine)manganese(I) dicarbonyl complexes 22 was realized by the molybdenum‐catalyzed ARCM, and the corresponding bridged planar‐chiral phosphacymantrene derivatives 23 were obtained in good yields with excellent enantioselectivity (Scheme 17). [33] Substrates 22 for this study possess an allylphosphine ligand and an η 5 ‐2,5‐bis(alkenyl)phospholide, where the two alkenyl substituents in the phospholide are identical and enantiotopic to each other. The enantioselectivity of the ARCM reaction was strongly influenced by the structures of the phospholyl‐bound alkenyl groups, and the highest enantioselectivity was achieved in the reaction of 22 e , which possesses the 2‐methylpropenyl substituents at the 2‐ and 5‐positions of the η 5 ‐phospholides, and ( R )‐ 23 e of 99 % ee was obtained in nearly quantitative yield.…”
Section: Planar‐chiral (η5‐cyclopentadienyl)manganese(i) Complexesmentioning
confidence: 99%